Identification of Fraud Triangle Theory to Mitigate Fraud Risks in Public Sector - Rismayani, Gista; Sukmana, Wawan; Somantri, Yeni Fitriani (Journal of International Conference Proceedings, 2023)
Fraudulence is an unethical act that can occur within both commercial and non-commercial contexts. This type of behavior involves intentional deception and can have serious negative consequences for individuals and organizations alike. This study aims to identify a fraud triangle to mitigate fraud risks in the public sector. The objects in this study are pressure, opportunity, rationalization, and fraud risk. The subject area is the public sector. The population is the villages in the Tasikmalaya Region. The method of sampling involves the use of probability sampling with a cluster sampling approach. The villages included in this study are located in the Cibalong sub-district: Cisempur, Setiawaras, Eureunpalay, Cibalong, Singajaya, and Parung—research methodology using a quantitative and survey approach. The data analysis used multiple regression analysis. The findings of this research are that pressure and opportunity have no significant effect but rationalization has a significant positive effect on risk fraud. The sustainability of the village can be ensured by promoting ethical behavior among village officials and enforcing punishment for fraud. Therefore, the central government must take action on this matter.